Penerapan Metode Convolution Neural Network (CNN) Pada Aplikasi Automatic Lip Reading - Nimatul Mamuriyah; Jason Sumantri (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
AbstractA Prototype of Automatic Lip-Reading or a prototype of automatic lip-reading is a device that is needed by people with hearing disabilities or the Deaf. The prototype will help people with hearing impairment move independently without depending on others. Advances in Nano technology have driven the development of Computer Vision and software that enables the creation of prototypes of Automatic Lip-Reading. The image processing applied to this prototype is focused on the movement of the lips, tongue, and the area around a person's mouth. Furthermore, the results of the image recognition will compare with the database that has been provided to produce certain words. The prototype design consists of a camera, Python with Tensorflow used as an image processing programming language with the Convolutional Neural Network (CNN) method as an image recognition method, and Machine Learning Technology used as processing and decision-making systems. This study, numbers and alphabets were used as trials or predictions of the Automated Lip-Reading system. By using CNN and Machine Learning methods, the test results show that in general, the system designed can predict numbers and alphabet with not quite high or less than 35%.